1986
DOI: 10.1126/science.3961499
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Supernumerary Chromosome in Cat Eye Syndrome

Abstract: Most individuals with cat eye syndrome (CES) have a supernumerary bisatellited chromosome which, on the basis of cytogenetic evidence, has been reported to originate from either chromosome 13 or 22. To resolve this question, a single-copy DNA probe, D22S9, was isolated and localized to 22q11 by in situ hybridization to metaphase chromosomes. The number of copies of this sequence was determined in CES patients by means of Southern blots and densitometry analysis of autoradiographs. In patients with the supernum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(54 citation statements)
references
References 5 publications
1
53
0
Order By: Relevance
“…In these studies, the level of mosaicism overall was reported to range from 13 to 50% (ave. 46%), but with B30% of the acrocentric SMCs compared with B70% of the nonacrocentric SMCs being classified as mosaics. 2,4,10,22,23 Further analyses of our data show that within the acrocentric SMCs, 20% of the SMC(15) and SMC (22) were mosaic compared with 31% for SMC (14) and 50% for SMC(13/21) respectively. Previous reports on SMC(15) have shown that on average B85% of SMC(15)s present as nonmosaics 13,24,28 and the majority of SMC (22) reported are also nonmosaics.…”
Section: Mosaicism and The Chromosomal Origins Of Smcsmentioning
confidence: 99%
“…In these studies, the level of mosaicism overall was reported to range from 13 to 50% (ave. 46%), but with B30% of the acrocentric SMCs compared with B70% of the nonacrocentric SMCs being classified as mosaics. 2,4,10,22,23 Further analyses of our data show that within the acrocentric SMCs, 20% of the SMC(15) and SMC (22) were mosaic compared with 31% for SMC (14) and 50% for SMC(13/21) respectively. Previous reports on SMC(15) have shown that on average B85% of SMC(15)s present as nonmosaics 13,24,28 and the majority of SMC (22) reported are also nonmosaics.…”
Section: Mosaicism and The Chromosomal Origins Of Smcsmentioning
confidence: 99%
“…Further, the breakpoints implicated in generating the cat eye chromosome, a supernumerary inverted duplication of proximal 22q implicated in cat eye syndrome (CES; MIM# 115470), frequently match the proximal LCR or one of the more distal LCRs of the 22q11.2 region [McDermid et al, 1986;Mears et al, 1994]. However, detailed analysis of the extent of the duplicated material and its relationship to the ensuing phenotype has been minimal.…”
Section: Introductionmentioning
confidence: 99%
“…Parental follow-up was not possible for this case. However, because Cat Eye syndrome is caused by a duplication of the proximal region of 22q11, which is usually observed as an additional marker chromosome, 29,30 but can also be seen as an interstitial duplication, 31-33 the 22q11 duplication detected by the array is likely to be related to this individual's phenotype. It also demonstrates that a microarray containing all clinically important target loci is useful for postnatal screening assays.…”
Section: Polymorphismsmentioning
confidence: 99%